Long-Term Comparative Outcomes of Patients With Peripheral Artery Disease With and Without Concomitant Coronary Artery Disease - Chen, Debbie C.; Singh, Gagan D.; Armstrong, Ehrin J.; Waldo, Stephen W.; Laird, John R.; Amsterdam, Ezra A. (The American journal of cardiology, 2017)
There are limited contemporary data on guideline-directed medical therapy (GDMT) utilization and long-term clinical outcomes in patients with peripheral artery disease (PAD) with and without concomitant coronary artery disease (CAD). From 2006 to 2013, 879 patients with claudication or critical limb ischemia (CLI) underwent diagnostic angiography or therapeutic endovascular intervention at our multidisciplinary vascular center. GDMT use was assessed at the time of angiography, and major adverse cardiovascular and cerebrovascular events (MACCE) and all-cause mortality were determined during 5 years of follow-up. Cox proportional hazard modeling was used to adjust for baseline differences between patients with and without concomitant CAD. Despite a higher adherence to GDMT (all p ≤0.002) for the use of aspirin, angiotensin-converting enzyme inhibitor/angiotensin receptor blocker, and statins, patients with PAD and concomitant CAD had higher unadjusted 5-year rates of MACCE (hazard ratio [HR] 1.7, 95% CI 1.3 to 2.1, p = 0.0001) and all-cause mortality (HR 1.86, 95% CI 1.4 to 2.4, p = 0.0001). After adjustment for baseline co-morbidities, the presence of CAD remained an independent risk factor for mortality (adjusted HR 1.35, 95% CI 1.02 to 1.80, p = 0.04) but not for MACCE (adjusted HR 1.24, 95% CI 0.96 to 1.60, p = 0.10) in patients with PAD. A sensitivity analysis limited to patients with CLI demonstrated that concomitant CAD was associated with significantly higher adjusted rates of both MACCE (adjusted HR 1.52, 95% CI 1.14 to 2.03, p = 0.01) and mortality (adjusted HR 1.64, 95% CI 1.12 to 2.20, p = 0.006). In conclusion, despite higher rates of GDMT use, PAD patients with concomitant CAD had significantly increased risk of all-cause mortality during a 5-year postprocedural follow-up. The subgroup of CLI patients with concomitant CAD was at particularly high risk for both MACCE and all-cause mortality.